Glances at Renewable and Sustainable Energy Principles, approaches and methodologies for an ambiguous benchmark - Jenssen, Till.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Differing interpretations, perspectives and expectations on the term sustainability exist. To take sustainability as an action guiding mandate for implementation, it needs to be concrete and measurable and it should weigh pros and cons. But how can such an integrated measurement in the field of renewable energy be conducted balancing the trade-offs between opposing indicators? Glances at Renewable and Sustainable Energy provides a thorough overview on the generic principles of sustainability assessment, including projective, thresholding and systemic principles and summarizes five common approaches for a holistic measurement. Approaches such as multi criteria decision analysis, ecological footprint analysis and normative-functional concepts are applied to different case studies in developed-, emerging and developing countries to cover a wide bandwidth of various renewable energy carriers under various conditions.   Compiling results on renewable energy assessment of the last decades, Glances at Renewable and Sustainable Energy gives researchers, students, consultants, politicians and entrepreneurs the tools to advance their oriental and instructional knowledge on sustainability and sustainability measurement, to reflect their decisions and tools for analysis and to transfer this knowledge into problem-solving.
1.Choosing sustainability? -- 2.Renewable Energy: Resources and Technologies -- 3.Multi-criteria decision analysis of renewable heating supply technologies in Germany -- 4.Ecological footprint:  the example of Gauteng region -- 5.Social Costs of on-shore wind energy in Europe -- 6.Guard rails for bioenergy in developed and developing countries -- 7.The normative-functional concept of sustainability and the question of indicator weights -- 8.A Kaleidoscope of Renewable and Sustainable Energy.
Keywords: Renewable energy resources; Environmental economics; Renewable and Green Energy; Renewable and Green Energy; Environmental Economics